Respostas

2013-11-12T10:49:01-02:00
X²-x-6=0a=1 b = -1   c = -6
Delta = (-1)² - 4 . (1) . (-6)
D = 1 +24
D= 25
x = -(-1) +-  = 25 / 2. (1)
x¹ = 1 + 5 = 6 / 2 = 3
x ¹¹ = 1-5 = -4 / 2 = -2
V = -2;3
2013-11-12T11:44:25-02:00
x2-x-6=0

A=1
B=-1
C=-6
DELTA=B2-4AC
DELTA=
(-1)2-4*1*(-6)
DELTA=1+24
DELTA=25

-(-1)+5       1+5                      -(-1)-5        1-5         -4
______ = ____ =    2              _______ = ______ = ___ = -2 
   2             2                            2             2           2